1994
DOI: 10.1007/bf02353198
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of nurturant parenting in teen mothers living in three generational families

Abstract: Direct and indirect effects of grandparents on maternal nurturance in teen mothers (TM) living in three-generational families were explored with path analytic techniques in a sample of 107 working-class families. Perceived support from the teen's mother, grandparents' nurturance toward the baby, and the presence of the grandfather as a father figure in the home were hypothesized as increasing TM nurturance. TM nurturance was found to be positively predicted by grandparent nurturance and negatively predicted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
10

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 48 publications
0
17
0
10
Order By: Relevance
“…For example, studies (e.g., Brooks-Gunn & Furstenberg, 1986;Cherlin & Furstenberg, 1986;Steven, 1984Steven, , 1988 identified that other family members' (e.g., grandmother, mother, and relatives) support for black adolescent single-parents serve as a positive impact on single mothers' educational achievement and economic betterment, which is also linked to their children's development (as cited in Taylor, Chatters, Tucker, & Lewis, 1990). Flaherty, Facteau, and Garver (1994) and Oyserman, Radin, and Saltz (1994) particularly identified that intergenerational support by Black grandmothers for child-rearing is a valuable resource to Black children's development (as cited in Lamborn & Nguyen, 2004). More recently, Lamborn and Nguyen found that kinship support is especially critical for the individual development of Black adolescents with a poor family background (e.g., low-income and low parental education level).…”
Section: Research Camped In Social Mobilization Perspectivementioning
confidence: 95%
“…For example, studies (e.g., Brooks-Gunn & Furstenberg, 1986;Cherlin & Furstenberg, 1986;Steven, 1984Steven, , 1988 identified that other family members' (e.g., grandmother, mother, and relatives) support for black adolescent single-parents serve as a positive impact on single mothers' educational achievement and economic betterment, which is also linked to their children's development (as cited in Taylor, Chatters, Tucker, & Lewis, 1990). Flaherty, Facteau, and Garver (1994) and Oyserman, Radin, and Saltz (1994) particularly identified that intergenerational support by Black grandmothers for child-rearing is a valuable resource to Black children's development (as cited in Lamborn & Nguyen, 2004). More recently, Lamborn and Nguyen found that kinship support is especially critical for the individual development of Black adolescents with a poor family background (e.g., low-income and low parental education level).…”
Section: Research Camped In Social Mobilization Perspectivementioning
confidence: 95%
“…Bronfenbrenner (1979Bronfenbrenner ( , 1986 contended that parents' informal and formal support systems constitute key influences in their childrearing. Several authorities have documented a positive association between social support and adjustment to parenthood for adult as well as adolescent mothers (Chase-Lansdale, Brooks-Gunn, & Zamsky, 1994;Jacobson & Frye, 1991;Oyserman, Radin, & Saltz, 1994;Unger & Wandersman, 1985). At 1 month postpartum, adolescent mothers with high instrumental support reportedly have a greater sense of competency in the maternal role (Mercer, Hackley, & Bostrom, 1984); and more child-care support is associated with higher quality interactions between mothers and babies (Levine, Garcia-Coll, & Oh, 1985).…”
Section: Maternal Chronological Age Childbearing and Childrearingmentioning
confidence: 99%
“…In the immediate surroundings, the quality of the parents' relationship with each other and mutual support seems to have a major effect on their conduct (Erel & Burman, 1995;Oyserman, Radin, & Saltz, 1994). The uncertain living conditions of teenaged mothers are thought to explain their high risk of maltreating their children (Bouchard & Desfossés, 1989;Buchholz & Korn-Bursztyn, 1993;Luster & Mittelstaedt, 1993).…”
Section: Risk Factorsmentioning
confidence: 96%